2016
DOI: 10.4172/2155-6156.1000504
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Paternal Transmission of Diabetes: Influence of Nutritional Factors

Abstract: Background: Pakistan is ranked at 6th place amongst the top 10 countries of the world. The number of estimated cases with diabetes in our country are 5.2 million in 2000 and projected to be 13.9 million in 2003. The objective of this research to examined risk for 2 diabetes and conditioned on directly ascertained parental diabetes status among population of Karachi, Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…According to latest estimates Pakistan has 7.2 million population of diabetes and projected to be 16.1 million by 2045 (Atlas 2017). Previous studies reported 5.2 million diabetic population of Pakistan in 2000 and projected to be 13.9 million till 2030 [16]. The worldwide prevalence of diabetes is shown in Figure 5.…”
Section: Epidemiologymentioning
confidence: 94%
“…According to latest estimates Pakistan has 7.2 million population of diabetes and projected to be 16.1 million by 2045 (Atlas 2017). Previous studies reported 5.2 million diabetic population of Pakistan in 2000 and projected to be 13.9 million till 2030 [16]. The worldwide prevalence of diabetes is shown in Figure 5.…”
Section: Epidemiologymentioning
confidence: 94%